Age, Race, and At-Risk Drinking in an HIV-infected U.S. Military Cohort. Issue 5 (24th January 2019) - Byrne, Morgan; Deiss, Robert; Mesner, Octavio; Glancey, Margaret; Ganesan, Anuradha; Okulicz, Jason; Kronmann, Karl; Maves, Ryan; Schofield, Christina; Agan, Brian; Macalino, Grace
Abstract: Introduction: There is a high prevalence of at-risk drinking in the U.S. military. Among HIV-infected individuals, alcohol abuse confers additional risk for adverse health outcomes. In the military, however, the characteristics of HIV-infected individuals who engage in high-risk drinking are not well defined. The purpose of this study was to assess risk factors associated with at-risk drinking in an HIV-positive longitudinal cohort of DoD beneficiaries. Materials and Methods: Annual prevalence of at-risk drinking was calculated for members of the U.S. Military HIV Natural History Study who initiated highly active antiretroviral therapy (HAART) during or after January 2006 through May 2014; each participant completed at least one self-reported alcohol survey within a year of HAART initiation. Univariate and multivariable logistic regression was used to analyze factors associated with at-risk drinking. Results: Sixty-six percent of subjects (495/752) reported at-risk drinking on at least one survey after HAART initiation. At-risk drinkers were more likely to be Active Duty compared to Retired (OR 0.65 95% CI [0.46, 0.92]). In multivariate models, Caucasian race (OR 3.30 95% CI [2.31, 4.71]); Hispanic/other race (OR 2.17 95% CI [1.51, 3.14]) and younger age (OR 0.61 per 10 years older, [95%CI 0.49, 0.75]) were significantly associated with at-risk drinking. Single relationship status (OR 1.51 95% CI [1.08, 2.13]) was also associated with at-risk drinking. Conclusions: Consistent with general alcohol consumption patterns in the military, we found a high prevalence of at-risk drinking among individuals with HIV infection, which was associated most closely with young, non-African Americans. Targeting interventions toward this group will be important to reduce at-risk drinking and its potential for HIV-related complications.